A high-strength tellurium-copper alloy material and preparation method thereof

By introducing magnesium, silver, rare earth yttrium and boron elements into tellurium copper alloy and carrying out specific heat treatment and deformation processing, the problem of low strength of tellurium copper alloy is solved, and a comprehensive improvement of high strength, hardness and wear resistance is achieved.

CN118389879BActive Publication Date: 2025-03-14SHAANXI PROVINCE MILITARY GRP SHAANXI COPPER
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410484123.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-22
Publication Date
2025-03-14
Estimated Expiration
2044-04-22

AI Technical Summary

Technical Problem

The strength of tellurium copper alloy is relatively low, which limits its application range, and it is difficult for the prior art to effectively improve its strength and hardness.

Method used

Magnesium, silver, rare earth yttrium and boron elements are introduced into the tellurium copper alloy, and solid solution and intermetallic compounds are formed through homogenized heat treatment, hot rolling, cold rolling and annealing processes to optimize the structural structure of the alloy.

Benefits of technology

It significantly improves the strength, hardness and wear resistance of tellurium copper alloy, while maintaining high conductivity and extending the service life of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of tellurium copper alloys, specifically to a high-strength tellurium copper alloy material and a preparation method thereof, comprising the following processes: taking electrolytic copper, pure yttrium, pure silver, copper-magnesium master alloy and copper-tellurium master alloy, mixing and smelting, casting to obtain a casting; performing homogenization heat treatment, hot rolling, cold rolling and annealing in sequence to obtain a tellurium copper alloy material. The present invention introduces silver and chromium elements into the tellurium copper alloy, and arranges homogenization heat treatment and hot rolling and cold rolling deformation processing, so that the prepared tellurium copper alloy can obtain higher mechanical properties while maintaining high electrical conductivity, thereby realizing the preparation of high-strength tellurium copper alloy. The present invention composites diamond with copper alloy, thermally sprays it on the surface of the tellurium copper alloy, and performs laser cladding to prepare a composite layer on the surface, thereby improving the surface thermal conductivity, wear resistance and corrosion resistance of the material, expanding the applicable environmental range of the material, and extending its service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-strength conductive tellurium-copper alloys, in particular to a high-strength tellurium-copper alloy material and a preparation method thereof. Background Art

[0002] Copper and its copper alloys are the earliest metal materials discovered and used by humans. They have excellent properties such as high electrical conductivity, high thermal conductivity, and easy processing. As an important basic material for the development of the national economy, they are widely used in many fields such as the electric power industry, information industry, aerospace, and rail transportation. Tellurium copper alloys have good electrical and thermal conductivity and arc erosion resistance, and are easy to process. However, the tellurium element exists in the form of a second phase Cu2Te at the grain boundary and inside the grain. This second phase is a soft phase with low hardness. Its pinning effect is easily eliminated during dislocation movement, and its strengthening effect on the copper alloy is not obvious. Its strength is low, which limits the application of tellurium copper alloys. Alloying is the main strengthening method of tellurium copper alloys. We propose a high-strength tellurium copper alloy material and a preparation method thereof. Summary of the invention

[0003] The object of the present invention is to provide a high-strength tellurium-copper alloy material and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a high-strength tellurium-copper alloy material, comprising the following processes:

[0005] Taking alloy raw materials, mixing, melting, and casting to obtain castings;

[0006] The homogenization heat treatment, hot rolling, cold rolling and annealing are carried out in sequence to obtain the tellurium copper alloy material.

[0007] Further, the tellurium-copper alloy material includes the following mass components: tellurium Te: 0.1% to 0.4%, silver Ag: 1.2 to 2.7, magnesium Mg: 0.3% to 0.6%, rare earth element (yttrium Y): 0.02% to 0.06%, boron B: 0.01% to 0.02%, phosphorus P: ≤0.012%, oxygen O: ≤0.06%, and the balance is copper Cu;

[0008] The alloy raw materials are electrolytic copper, pure yttrium, pure silver, copper-magnesium master alloy and copper-tellurium master alloy.

[0009] Furthermore, in the tellurium-copper alloy material, the total mass of magnesium Mg and tellurium Te elements is ≤0.8%.

[0010] In the above technical solution, magnesium is introduced into the tellurium copper alloy, and magnesium is limitedly dissolved in the copper matrix to form a solid solution, occupying the interstitial position of the octahedron or tetrahedron in the lattice, so that the lattice in the copper matrix is ​​distorted, increasing the resistance to dislocation slip, thereby playing a solid solution strengthening role, which can effectively improve the strength and hardness of the copper alloy and improve its wear resistance. The addition of magnesium can promote the refinement and dispersion of grains in the copper matrix, optimize the organizational structure of the copper alloy, improve the plasticity and toughness of the alloy; and can inhibit the electrochemical reaction of the metal and improve the corrosion resistance of the copper alloy. In smelting, magnesium can also be used as a deoxidizer to degas and deoxidize the melt, improve the quality of the tellurium copper alloy; and improve the high temperature oxidation resistance and recrystallization temperature of the tellurium copper alloy. However, the distortion caused by the solid solution strengthening brought by magnesium will scatter the movement of electrons and affect the conductivity of the alloy.

[0011] Silver has a relatively high electrical conductivity and can effectively improve the electrical conductivity of tellurium copper alloys and alleviate the decrease in conductivity caused by the process. It dissolves in the copper matrix to enhance the strength and hardness of the copper alloy, improve its wear resistance and fatigue resistance, and avoid deformation and plastic degradation of the copper alloy. The silver phase dispersed in the copper alloy has high ductility and can form filaments through deformation, improving the tensile properties of the alloy; it can also effectively improve the corrosion resistance of the copper alloy, has good anti-corrosion properties, and prolongs its service life. The silver element can also form a structurally stable intermetallic compound silver-magnesium phase with the magnesium element, which has good resistance to deformation and shearing, and helps to further improve the strength of the tellurium copper alloy.

[0012] The rare earth yttrium element can react with impurity elements to remove oxygen O, phosphorus P and other impurity elements in the tellurium copper alloy, reduce the solid solubility of the impurity elements in the copper matrix, facilitate the smooth discharge of impurity products, purify the melt composition and grain boundaries, and improve the plasticity of the alloy material; it can also alleviate the degree of lattice distortion in the copper matrix, reduce the probability of electron scattering, and improve the conductivity of the tellurium copper alloy to a certain extent. Rare earth yttrium can also refine the grains, concentrate the grain boundaries inside the metal, prevent the grains from growing, thereby refining the alloy structure, increasing the movement resistance of dislocations, allowing yttrium to play a fine grain strengthening role and improve the mechanical properties of the tellurium copper alloy.

[0013] The element boron can react with iron under high temperature conditions to achieve the effect of iron removal and refine the grains in the copper matrix. Boron can also form intermetallic compounds with magnesium, which as a second phase helps to improve the yield strength and tensile strength of magnesium-tellurium-copper alloys; it can also eliminate the coarse columnar crystals of the alloy, refine the grains, and further improve its yield strength.

[0014] The synergistic addition of rare earth elements yttrium and boron into the tellurium copper alloy allows small and high-hardness intermetallic compound YB6 particles and metal oxide Y2O3 and B2O3 particles to remain in the alloy melt, which can be dispersed in the casting, increase the matrix's resistance to dislocation slip, and improve the strength of the tellurium copper alloy.

[0015] Further, the smelting temperature is 1180-1230°C;

[0016] In the smelting process, firstly preheat the electric furnace to 500℃±20℃, preheat the alloy raw materials to 300℃±20℃, and dry the deoxidizer and covering agent to constant weight;

[0017] Then, electrolytic copper is added into the electric furnace, covered with a covering agent, heated until completely melted, and a deoxidizer is added for deoxidation treatment; the alloy raw material covered with copper foil is pressed into the bottom of the solution to melt;

[0018] The deoxidizer is a mixture of phosphor copper alloy and calcium hexaboride, and the addition amounts are 0.03% to 0.04% and 0.72% to 1.12% of the total mass of the alloy raw materials respectively;

[0019] The covering agent is flake graphite.

[0020] Furthermore, the casting adopts electromagnetic casting, and the specific process conditions are: casting temperature is 1190-1220°C, electromagnetic power is 12-15kW; mold preheating is 200-500°C.

[0021] In the above technical scheme, electromagnetic continuous casting is adopted, and an induced current is generated in the melt. The induced current interacts with the magnetic field, and the electromagnetic field formed points to the axis of the liquid column, which is opposite to the static pressure direction of the melt, and helps to make the surface of the produced casting smooth. Under the influence of electromagnetic force, the fluidity of the melt increases, and the distribution of alloy elements and second-phase intermetallic compounds in the copper matrix is ​​more dispersed, which can alleviate the segregation phenomenon of alloy elements between dendrites; and can promote the discharge of internal gas and the floating of impurities, reduce the number of pores and impurities in the casting, increase the density of the casting, and improve its mechanical properties. In the solidification stage of the melt, the crystals and dendrites generated at the solid-liquid interface fall off and break under the stirring of electromagnetic force, forming crystal nuclei and suspending in the melt, which can inhibit the growth of columnar crystal areas; the crystal nuclei, as the nucleation core of equiaxed crystals, expand the equiaxed crystal area, refine the grains, and greatly increase the grain boundary area per unit area of ​​the casting, and improve its tensile strength and elongation. Under the action of the electromagnetic field, some Cu2Te particle phases originally distributed at the grain boundaries are reduced, which reduces the resistance of free electrons in the migration process. Due to the significant grain refinement, the grain boundary area is greatly increased, which increases the scattering probability of free electrons. The two effects offset each other and the conductivity of the alloy does not change significantly.

[0022] Furthermore, the process conditions of the homogenization heat treatment are: heat treatment temperature 676-726° C., and insulation time 2-4 hours.

[0023] In the above technical scheme, the casting obtained in the previous step is subjected to homogenization heat treatment to alleviate the uneven distribution of alloy elements in the casting, reduce the segregation of alloy elements in the interdendritic gap, promote the diffusion of alloy elements from high concentration to low concentration area, realize the homogenization of alloy elements, and give full play to the solid solution strengthening and precipitation strengthening effects of magnesium and silver elements in tellurium copper alloy. The degree of distortion of the lattice periodic potential field is aggravated, the resistance to dislocation movement is increased, and the yield strength of the casting is enhanced, which is manifested as an increase in Vickers hardness. The magnesium element in the copper matrix can also be dissolved with silver, hindering the growth of magnesium grains, helping to reduce its grain size and improve the strength and hardness of the casting. With the increase of the homogenization heat treatment process temperature and the extension of the treatment time, the distribution of alloy elements in the casting is more uniform. However, too long homogenization time and too high treatment temperature will cause the internal grains of the alloy to grow, the degree of lattice distortion to be alleviated, and the hardness to decrease. At high temperatures, the oxygen O present in the casting dissociates and adsorbs, reacting with the oxygen-affinity element magnesium to produce dispersed oxide particles, which expands the alloy lattice parameters, increases residual stress, hinders dislocation movement, improves the hardness and strength of the casting, and improves the wear resistance and conductivity of the alloy.

[0024] Furthermore, the hot rolling process conditions are: hot rolling temperature 840-870°C, single-pass reduction 5%-20%, total deformation 50%-70%; room temperature water quenching after hot rolling.

[0025] Furthermore, the process conditions of the cold rolling are: a single-pass reduction of 1% to 25%, and a total cold rolling deformation of 50% to 90%.

[0026] In the above technical solution, the casting obtained after homogenization heat treatment is deformed. Affected by the pressure of hot rolling treatment, the columnar crystals in the casting are broken, the grain size in the organization decreases, tends to be fine, dense, and uniform, and transforms to fine and uniform equiaxed crystals, with obvious fine grain strengthening effect; and it can eliminate casting defects such as pores and shrinkage in the organization.

[0027] Cold rolling causes the grains in the alloy structure to be flattened and elongated along the rolling direction, causing slippage, blurring the grain boundaries, and showing an obvious fibrous structure in the matrix; the second phase is elongated along the cold rolling direction, presenting a chain or strip shape; the dislocation density increases, causing dislocation accumulation, entanglement between dislocations, and increasing the difficulty of dislocation slip. At the same time, the accumulation of dislocations around the second phase particles makes the strip-shaped second phase easy to be broken by dislocations, deforming and dragging along with the alloy matrix, achieving the refinement of the tellurium copper alloy structure, increasing the tensile strength of the alloy, decreasing the elongation, and causing work hardening. And with the increase in deformation, the size of the alloy structure decreases, the arrangement becomes finer, and the distribution becomes more uniform. The higher dislocation density causes the matrix to recrystallize. Under stress, the organization is arranged in parallel along the cold rolling direction, twins and stacking faults appear, and the grains are cold-rolled from spherical to fibrous and long strips, which helps to improve the strength and hardness of the tellurium copper alloy.

[0028] Furthermore, the annealing process conditions are: annealing temperature 360-390° C., and insulation time 30-60 min.

[0029] In the above technical solution, annealing treatment puts the alloy in the recovery stage, maintaining the organizational state and mechanical properties after rolling. Thermal energy causes dislocations in the crystal to diffuse and migrate, dislocations to rearrange regularly, point defect concentration to decrease, and conductivity to increase. However, too high a temperature and too long a holding time will cause the alloy to recrystallize, increase the grain boundary area, intensify electron scattering, and affect conductivity.

[0030] Furthermore, the surface of the casting is subjected to surface treatment, and the process is: using thermal spraying to spray copper / diamond composite powder on the surface of the casting to form a coating; laser cladding to form a composite layer.

[0031] Furthermore, the process conditions of thermal spraying are: arc current 250-300A, voltage 30-50V, powder feeding rate 28-30g / min, spraying distance 90-100mm; argon gas flow rate 2.0m 3 / h, hydrogen flow rate 0.2m 3 / h;

[0032] Spraying thickness 80~130μm.

[0033] Furthermore, the process conditions of the laser cladding are: laser power 825-1000W, scanning rate 8-13mm / s, spot diameter 3-5mm, overlap rate 10%-30%.

[0034] Furthermore, the copper / diamond composite powder is prepared by the following process:

[0035] Chromium powder, nickel powder and diamond are added with anhydrous ethanol and mixed, placed in a tube furnace, heated to 940-980°C at a heating rate of 10°C / min, and kept warm for 70-120min; cooled to room temperature at a rate of 10°C / min; crushed to obtain diamond composite powder with a particle size of 20-40μm;

[0036] Mixed with copper powder to obtain copper / diamond composite powder.

[0037] Further, the mass ratio of diamond, chromium powder and nickel powder is 1:(1.2-2.1):(6.3-8.7);

[0038] The mass ratio of diamond to copper powder is (1.6-2.7):100;

[0039] The volume ratio of the total volume of diamond, chromium powder and nickel powder to anhydrous ethanol is 1:(0.7-1.2).

[0040] In the above technical scheme, a copper alloy containing diamond (referred to as copper / diamond composite powder in this application) is sprayed on the surface of the casting by a thermal spraying process, and then laser cladding is used to melt and homogenize the components in the composite powder, and the coating is overlapped with the surface of the tellurium copper alloy to cause metal mutual melting, achieve metallurgical bonding, and form a composite layer. The matrix of the composite layer is a copper-nickel alloy, and chromium is added, which can maintain the high strength and high conductivity of the material, while improving the corrosion resistance of the tellurium copper alloy material in this application and expanding the applicable environmental range of the material. Using diamond as a carbon reinforcement phase significantly improves the strength and hardness of the composite layer, which can effectively improve the surface thermal conductivity, mechanical properties and wear resistance of the tellurium copper alloy material in this application, and extend its service life.

[0041] There are unpaired electrons in the empty d orbitals of nickel and chromium atoms. Free electrons have extremely high chemical activity and are easy to form chemical adsorption with diamond atoms. Diamond is mixed with nickel and chromium for heat treatment. At high temperature, the metal atoms contact and adsorb on the diamond surface, wet the rough and defective parts of the diamond surface, produce point defects, break the sp3 bond of diamond, and induce the formation of more stable sp2 carbon-carbon bonds. Driven by the concentration difference, the metal diffuses and moves away from the enriched area, reforming the carbon-metal interface and forming a graphite layer on the diamond surface, thereby increasing the surface defects of the diamond, helping to increase the contact area between the diamond and the metal alloy, improving the bonding force between the diamond and the copper-nickel alloy, enhancing the heat conduction channel between the two, and improving the comprehensive performance of the composite layer.

[0042] The composite layer is deformed with the casting, and is hot-rolled and cold-rolled in sequence. The thickness of the composite layer is significantly reduced, which can alleviate the conductivity difference between the two and maintain the high conductivity of the tellurium copper alloy material; the grain size is refined, and the mechanical properties and wear resistance of the composite layer are improved. Under the influence of rolling, the metallurgical bonding between the composite layer and the tellurium copper alloy material interface is enhanced, which promotes the diffusion of metal atoms and further improves the mechanical properties, corrosion resistance and wear resistance of the material.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] 1. A method for preparing a high-strength tellurium-copper alloy material of the present invention introduces silver and chromium elements into the tellurium-copper alloy, and arranges homogenization heat treatment and hot rolling and cold rolling deformation processing, so that the prepared tellurium-copper alloy can obtain higher mechanical properties while maintaining high electrical conductivity, thereby realizing the preparation of high-strength tellurium-copper alloy.

[0045] 2. The present invention provides a method for preparing a high-strength tellurium-copper alloy material. Diamond and copper alloy are composited, thermally sprayed on the surface of the tellurium-copper alloy, and laser cladding is performed to prepare a composite layer on the surface, thereby further improving the strength and hardness of the material. At the same time, the surface thermal conductivity, wear resistance, and corrosion resistance of the material are improved, thereby expanding the applicable environmental range of the material and extending its service life. DETAILED DESCRIPTION

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] In the following specific implementations:

[0048] Electrolytic copper: purity 99.99%; pure yttrium: purity ≥99.8%; pure silver: purity 99.9%; copper-magnesium master alloy: Cu-20.1%Mg; copper-tellurium master alloy: Cu-66.8%Te;

[0049] Chromium powder: particle size ≤10μm, purity ≥99.5%; nickel powder: particle size ≤10μm, purity ≥99.9%; copper powder: particle size ≥325 mesh, purity 99.9%, sourced from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0050] Diamond: average particle size 6μm, sourced from Henan Huanghe Cyclone Co., Ltd.;

[0051] In the following smelting process, firstly, the electric furnace is preheated to 500°C, the alloy raw material is preheated to 300°C, and the deoxidizer and covering agent are dried to constant weight; then, the electrolytic copper is added into the electric furnace, the covering agent is added to cover it, heated until it is completely melted, and the deoxidizer is added for deoxidation treatment; the alloy raw material coated with copper foil is pressed into the bottom of the solution to melt; the deoxidizer is a mixture of phosphor copper alloy and calcium hexaboride, and the addition amount is 0.035% and 0.9 of the total mass of the alloy raw material respectively; phosphor copper alloy: Cu-14.3%P, and the covering agent is flake graphite.

[0052] In Examples 1-3, the castings include the following mass compositions: tellurium: 0.27%, silver: 2.1, magnesium: 0.50%, yttrium: 0.04%, boron: 0.013%, phosphorus: 0.004%, oxygen: 0.019%, and the balance is copper.

[0053] Embodiment 1: A method for preparing a high-strength tellurium-copper alloy material, comprising the following process:

[0054] (1) electrolytic copper, pure yttrium, pure silver, copper-magnesium master alloy and copper-tellurium master alloy are mixed and smelted at 1180° C.; casting is performed by electromagnetic continuous casting, the casting temperature is 1190° C., and the electromagnetic power is 15 kW; the mold is preheated to 200° C. to obtain a casting;

[0055] (2) adding chromium powder, nickel powder and diamond to anhydrous ethanol, placing the mixture in a tube furnace, heating the mixture to 940°C at a heating rate of 10°C / min, and keeping the temperature for 120 min; cooling the mixture to room temperature at a rate of 10°C / min; crushing the mixture to obtain a diamond composite powder having an average particle size of 40 μm; mixing the mixture with copper powder to obtain a copper / diamond composite powder; the mass ratio of diamond, chromium powder and nickel powder is 1:1.2:6.3; the mass ratio of diamond to copper powder is 2.7:100; the volume ratio of the total volume of diamond, chromium powder and nickel powder to anhydrous ethanol is 1:0.7;

[0056] The copper / diamond composite powder was sprayed on the casting surface by thermal spraying to form a coating. The process conditions of thermal spraying were as follows: arc current 250A, voltage 30V, powder feeding rate 28g / min, spraying distance 90mm, argon flow rate 2.0m3 / h, hydrogen flow rate 0.2m3 / h.

[0057] Laser cladding, the process conditions of laser cladding are: laser power 825W, scanning rate 8mm / s, spot diameter 3mm, overlap rate 10%, forming a composite layer;

[0058] (3) placing at 676°C for 4 hours for homogenization heat treatment; hot rolling, the hot rolling temperature is 840°C, the single-pass reduction is 5% to 20%, and the total deformation is 50%; after the hot rolling, water quenching at room temperature; cold rolling, the single-pass reduction is 1% to 25%, and the total cold rolling deformation is 90%; annealing heat treatment is carried out at 360°C for 60 minutes to obtain a tellurium copper alloy material.

[0059] Embodiment 2: A method for preparing a high-strength tellurium-copper alloy material, comprising the following process:

[0060] (1) electrolytic copper, pure yttrium, pure silver, copper-magnesium master alloy and copper-tellurium master alloy are mixed and smelted at 1200° C.; casting is performed by electromagnetic continuous casting, the casting temperature is 1200° C., and the electromagnetic power is 14 kW; the mold is preheated at 350° C. to obtain a casting;

[0061] (2) Chromium powder, nickel powder and diamond were added to anhydrous ethanol and mixed, and placed in a tube furnace, and heated to 960°C at a heating rate of 10°C / min, and kept warm for 95 minutes; cooled to room temperature at a rate of 10°C / min; crushed to obtain a diamond composite powder with an average particle size of 30 μm; mixed with copper powder to obtain a copper / diamond composite powder; the mass ratio of diamond, chromium powder and nickel powder was 1:1.6:7.5; the mass ratio of diamond to copper powder was 2.1:100; the volume ratio of the total volume of diamond, chromium powder and nickel powder to anhydrous ethanol was 1:1;

[0062] The copper / diamond composite powder was sprayed on the casting surface by thermal spraying to form a coating. The process conditions of thermal spraying were as follows: arc current 270A, voltage 40V, powder feeding rate 29g / min, spraying distance 95mm, argon flow rate 2.0m3 / h, hydrogen flow rate 0.2m3 / h.

[0063] Laser cladding, the process conditions of laser cladding are: laser power 910W, scanning rate 10mm / s, spot diameter 4mm, overlap rate 20%, forming a composite layer;

[0064] (3) placing at 700°C for 3 hours for homogenization heat treatment; hot rolling, the hot rolling temperature is 850°C, the single pass reduction is 5% to 20%, and the total deformation is 60%; after the hot rolling, water quenching at room temperature; cold rolling, the single pass reduction is 1% to 25%, and the total cold rolling deformation is 70%; annealing heat treatment is carried out at 375°C for 45 minutes to obtain a tellurium copper alloy material.

[0065] Embodiment 3: A method for preparing a high-strength tellurium-copper alloy material, comprising the following process:

[0066] (1) electrolytic copper, pure yttrium, pure silver, copper-magnesium master alloy and copper-tellurium master alloy are mixed and smelted at 1230° C.; casting is performed by electromagnetic continuous casting, the casting temperature is 1220° C., and the electromagnetic power is 12 kW; the mold is preheated to 500° C. to obtain a casting;

[0067] (2) Chromium powder, nickel powder and diamond were added to anhydrous ethanol and mixed, placed in a tube furnace, heated to 980°C at a heating rate of 10°C / min, and kept warm for 70 minutes; cooled to room temperature at a rate of 10°C / min; crushed to obtain a diamond composite powder with an average particle size of 20 μm; mixed with copper powder to obtain a copper / diamond composite powder; the mass ratio of diamond, chromium powder and nickel powder was 1:2.1:8.7; the mass ratio of diamond to copper powder was 1.6:100; the volume ratio of the total volume of diamond, chromium powder and nickel powder to anhydrous ethanol was 1:1.2;

[0068] The copper / diamond composite powder was sprayed on the casting surface by thermal spraying to form a coating. The process conditions of thermal spraying were as follows: arc current 300A, voltage 50V, powder feeding rate 30g / min, spraying distance 100mm, argon flow rate 2.0m3 / h, hydrogen flow rate 0.2m3 / h.

[0069] Laser cladding, the process conditions of laser cladding are: laser power 1000W, scanning rate 13mm / s, spot diameter 5mm, overlap rate 30%, forming a composite layer;

[0070] (3) placing at 726°C for 2 hours for homogenization heat treatment; hot rolling, the hot rolling temperature is 870°C, the single-pass reduction is 5% to 20%, and the total deformation is 70%; after the hot rolling, water quenching at room temperature; cold rolling, the single-pass reduction is 1% to 25%, and the total cold rolling deformation is 50%; annealing heat treatment is carried out at 390°C for 30 minutes to obtain a tellurium copper alloy material.

[0071] Comparative Example 1: The composition and preparation process of the casting are the same as those of Example 1.

[0072] (2) mixing diamond and copper powder to obtain copper / diamond composite powder; the mass ratio of diamond to copper powder is 2.7:100;

[0073] The copper / diamond composite powder was sprayed on the casting surface by thermal spraying to form a coating. The process conditions of thermal spraying were as follows: arc current 250A, voltage 30V, powder feeding rate 28g / min, spraying distance 90mm, argon flow rate 2.0m3 / h, hydrogen flow rate 0.2m3 / h.

[0074] Laser cladding: The process conditions of laser cladding are as follows: laser power 825W, scanning rate 8mm / s, spot diameter 3mm, overlap rate 10%, forming a composite layer to obtain tellurium copper alloy material.

[0075] Comparative Example 2: The composition and preparation process of the casting are the same as those of Example 1.

[0076] (2) Preparation of composite layer:

[0077] The diamond and copper powder are mixed to obtain copper / diamond composite powder; the mass ratio of diamond to copper powder is 2.7:100;

[0078] The copper / diamond composite powder was sprayed on the casting surface by thermal spraying to form a composite layer to obtain a tellurium copper alloy material. The thermal spraying process conditions were: arc current 250A, voltage 30V, powder feeding rate 28g / min, spraying distance 90mm; argon gas flow rate 2.0m 3 / h, hydrogen flow rate 0.2m 3 / h.

[0079] Comparative Example 3: A method for preparing a high-strength tellurium-copper alloy material, comprising the following processes:

[0080] (1) electrolytic copper, pure yttrium, pure silver, copper-magnesium master alloy and copper-tellurium master alloy are mixed and smelted at 1180° C.; casting is performed by electromagnetic continuous casting, the casting temperature is 1190° C., and the electromagnetic power is 15 kW; the mold is preheated to 200° C. to obtain a casting;

[0081] (2) placing at 676°C for 4 hours for homogenization heat treatment; hot rolling, the hot rolling temperature is 840°C, the single pass reduction is 5% to 20%, and the total deformation is 50%; after the hot rolling, water quenching at room temperature; cold rolling, the single pass reduction is 1% to 25%, and the total cold rolling deformation is 90%; annealing heat treatment is carried out at 360°C for 60 minutes to obtain a tellurium copper alloy material.

[0082] Comparative Example 4: The preparation process of the tellurium-copper alloy material is the same as that of Comparative Example 3, and the tellurium-copper alloy material includes the following mass components: tellurium: 0.27%, silver: 2.1, magnesium: 0.82%, yttrium: 0.04%, boron: 0.010%, phosphorus: 0.003%, oxygen: 0.028%, and the balance is copper; it is placed at 676°C for 4 hours for homogenization heat treatment; it is kept at 360°C for 60 minutes for annealing heat treatment to obtain the tellurium-copper alloy material.

[0083] Comparative Example 5: The preparation process of the tellurium-copper alloy material is the same as that of Comparative Example 3. The tellurium-copper alloy material includes the following mass components: tellurium: 0.26%, yttrium: 0.05%, boron: 0.017%, phosphorus: 0.007%, oxygen: 0.028%, and the balance is copper; the material is annealed at 390°C for 60 minutes to obtain the tellurium-copper alloy material.

[0084] Experiment: The tellurium copper alloy materials obtained in Examples 1-3 and Comparative Examples 1-5 were used to prepare samples, and their properties were tested and the test results were recorded:

[0085] Hardness test: The micro-Vickers hardness of the tellurium copper alloy material sample was tested using a Vickers hardness tester with a load of 4.9N and a loading time of 30s;

[0086] Tensile performance test: The tensile performance of the sample was tested at room temperature using an electronic universal material testing machine with a tensile rate of 2 mm / min.

[0087] Conductivity test: The conductivity of the sample was tested using a metal conductivity meter. The sample size was 20mm×20mm×10mm.

[0088] Vickers hardness (HV) Tensile strength(MPa) Elongation(%) Electrical conductivity (%IACS) Example 1 208 640.3 8.3 69.0 Example 2 220 630.7 7.6 71.6 Example 3 235 626.2 6.8 73.7 Comparative Example 1 203 637.4 8.7 68.6 Comparative Example 2 192 619.5 9.3 67.8 Comparative Example 3 165 547.6 9.8 75.3 Comparative Example 4 145 481.0 14.3 90.8 Comparative Example 5 130 207.5 33.4 72.6

[0089] According to the data in the above table, we can clearly draw the following conclusions:

[0090] The tellurium-copper alloy materials obtained in Examples 1-3 and the tellurium-copper alloy materials obtained in Comparative Examples 1-5 are compared, and the test results show that:

[0091] Compared with the comparative example, the tellurium copper alloy materials obtained in Examples 1-3 have better Vickers hardness and tensile strength, and maintain relatively good electrical conductivity. The improvement of the surface hardness of the material is conducive to the improvement of its wear resistance. This fully demonstrates that the present invention achieves the improvement of the strength of the tellurium copper alloy material, improves the wear resistance of the material, and maintains its electrical conductivity.

[0092] Compared with Example 1, the diamond in Comparative Example 1 was not mixed with chromium powder and nickel powder for heat treatment, and the copper / diamond composite powder was obtained by mixing diamond and copper powder; the composite layer in Comparative Example 2 was obtained by thermal spraying the copper / diamond composite powder made of diamond and copper powder; and no composite layer was set in Comparative Example 3. Compared with Comparative Example 3, the tellurium copper alloy materials obtained in Comparative Examples 4-5 have different components. It can be seen from the above data that the Vickers hardness and tensile strength data of the tellurium copper alloy materials obtained in Comparative Examples 1-5 are significantly reduced. The setting of the preparation process of the tellurium copper alloy material and the components used in this application promotes the improvement of material strength and wear resistance.

[0093] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0094] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-strength tellurium-copper alloy material, characterized in that: Including the following processes: Electrolytic copper, pure yttrium, pure silver, copper-magnesium master alloy and copper-tellurium master alloy are mixed, smelted, and cast to obtain a casting; Performing homogenization heat treatment, hot rolling, cold rolling, and annealing in sequence to obtain a tellurium copper alloy material; The surface of the casting is subjected to surface treatment, and the process is: using thermal spraying to spray copper / diamond composite powder on the surface of the casting to form a coating; laser cladding to obtain a composite layer; The copper / diamond composite powder is prepared by the following process: Chromium powder, nickel powder and diamond are added with anhydrous ethanol and mixed, placed in a tube furnace, heated to 940-980°C at a heating rate of 10°C / min, and kept warm for 70-120min; cooled to room temperature at a rate of 10°C / min; crushed to obtain diamond composite powder with a particle size of 20-40μm; mixed with copper powder to obtain copper / diamond composite powder; The tellurium-copper alloy material comprises the following mass components: tellurium: 0.1% to 0.4%, silver: 1.2% to 2.7%, magnesium: 0.3% to 0.6%, yttrium: 0.02% to 0.06%, boron: 0.01% to 0.02%, phosphorus: ≤0.012%, oxygen: ≤0.06%, and the balance is copper; In the tellurium-copper alloy material, the total mass of magnesium and tellurium elements is ≤0.8%.

2. The method for preparing a high-strength tellurium-copper alloy material according to claim 1, characterized in that: The melting temperature is 1180~1230℃; The casting adopts electromagnetic continuous casting, and the process conditions are: casting temperature is 1190-1220°C, electromagnetic power is 12-15kW; mold preheating is 200-500°C.

3. The method for preparing a high-strength tellurium-copper alloy material according to claim 1, characterized in that: The process conditions of the homogenization heat treatment are: heat treatment temperature 676-726°C, heat preservation time 2-4h; The annealing process conditions are: annealing temperature 360-390° C., and heat preservation time 30-60 min.

4. The method for preparing a high-strength tellurium-copper alloy material according to claim 1, characterized in that: The hot rolling process conditions are as follows: hot rolling temperature is 840-870°C, single-pass reduction is 5%-20%, and total deformation is 50%-70%; The process conditions of the cold rolling are as follows: the reduction amount of a single pass is 1% to 25%, and the total deformation amount of the cold rolling is 50% to 90%.

5. The method for preparing a high-strength tellurium-copper alloy material according to claim 1, characterized in that: The process conditions of the thermal spraying are: arc current 250-300A, voltage 30-50V, powder feeding rate 28-30g / min, spraying distance 90-100mm; The process conditions of the laser cladding are: laser power 825-1000W, scanning speed 8-13mm / s, spot diameter 3-5mm, and overlap rate 10%-30%.

6. The method for preparing a high-strength tellurium-copper alloy material according to claim 1, characterized in that: The mass ratio of diamond, chromium powder and nickel powder is 1:(1.2-2.1):(6.3-8.7); The mass ratio of diamond to copper powder is (1.6-3.4):

100.

7. A high-strength tellurium-copper alloy material prepared according to the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • High-strength high-conductivity electrical copper alloy and processing method thereof

    CN106282645A

  • Method of laser cladding copper-based diamond particle reinforced composite coating on copper alloy surface

    CN111424270A